2022
DOI: 10.1002/mame.202200010
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing based on Photopolymerization and Photocatalysts: Review and Prospect

Abstract: 3D printing is a fabrication method that has attracted worldwide attention in recent years, providing a convenient and economical method for the fabrication of 3D structures. With the development of this technology and the reduction of operating costs, the application of 3D printing is greatly expanded. This paper focuses on the application progress of 3D printing in the preparation of photocatalysts. Considering the advantage that photopolymerization-based 3D printing technology can better control the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…Emerging data have shown that environmental factors such as oxygen levels can affect the angiogenic properties of stem cell Exos [ 287 ]. Zhu and colleagues investigated the angiogenic and immunomodulatory properties of adipose-derived stem cell (ASC) Exos under normoxic and hypoxic conditions in a mouse model of the ischemic hind limb (Fig.…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%
See 3 more Smart Citations
“…Emerging data have shown that environmental factors such as oxygen levels can affect the angiogenic properties of stem cell Exos [ 287 ]. Zhu and colleagues investigated the angiogenic and immunomodulatory properties of adipose-derived stem cell (ASC) Exos under normoxic and hypoxic conditions in a mouse model of the ischemic hind limb (Fig.…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%
“…Zhu and colleagues investigated the angiogenic and immunomodulatory properties of adipose-derived stem cell (ASC) Exos under normoxic and hypoxic conditions in a mouse model of the ischemic hind limb (Fig. 3 ) [ 287 ]. Data indicated that ASC Exos can promote M2-type macrophage polarization (CD206 + cells), and suppress CD86 macrophages.…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%
See 2 more Smart Citations
“…In DLP printing, the resin solution used to create 3D objects does not require precise adjusting for physicochemical qualities, including viscosity and surface tension. [30] Fabrication of luminous 3D structures, extremely stretchy photopolymers, designed nerve guiding conduits, re-processable Reproduced under the terms of CC BY 4.0 license. [33] Copyright 2020, The Authors, published by WHIOCE.…”
Section: Digital Light Processing (Dlp)-based Printingmentioning
confidence: 99%